The early medieval settlement complex at Czermno in the light of results from past research (up to 2010) : Material evidence = Wczesnośredniowieczny zespół osadniczy w Czermnie w świetle wyników badań dawnych (do 2010) : Podstawy źródłowe - Florek, Marek; Wołoszyn, Marcin (2016)
This book (in two volumes) presents research papers on the subject of the hillfort at Czermno, on Poland's eastern border, identified at present as the remains of the early medieval city of Cherven', a major site on the Polish-Ruthenian borderland in the 10th–13th centuries. The present book discusses the results of archaeological fieldwork made at Czermno in the past (1940, 1952, 1974–1979, 1985 and 1997) and of the latest geophysical surveys, earth sciences (geography and geology) and nature sciences (archaeozoology, palaeobotany) analyses and technological studies (textile analysis, metallography). A separate study discusses the written and cartographic sources for the history of Czermno-Cherven'. Individual analyses are the result of an international cooperation of researchers from Poland, Germany, Russia, Serbia and Ukraine pursued within two wide-scale projects: The Golden Apple of Polish archaeology. Stronghold complexes at Czermno and Gródek (Cherven' towns) – chronology and function in the light of past and current research (Ministry of Science and Higher Education, Warsaw/Poland; National Programme for the Development of the Humanities; project No. 12H 12 0064 81), and The Elbe Marches, Poland and Bohemia from the 10th to the 12th century (Federal Ministry of Education and Research, Bonn/Germany; project No. FKZ 01UG1410)